Determinan Aklimatisasi Tubuh Pada Jemaah Haji Indonesia - Elwindra Elwindra (STIKes Persada Husada Indonesia, 2020)
Activities carried out by pilgrims every day from morning to evening. During the day, the scorching heat that occurs right before the midday prayer until Asr prayer has the potential to make Indonesian pilgrims who are accustomed to experiencing tropical temperatures with a maximum heat of 34 degrees Celsius, are threatened with dehydration which can lead to heat stroke or heat stroke. Exposure to heat for hours disrupts the body's balance system, where the body excretes sweat as a compensatory mechanism. This paper aims to determine factors related to acclimatization due to heat stress on Indonesian pilgrims. This study is a further analysis of the Hajj Health Services Research data. Further analysis was carried out in 2021. The research design used was cross-sectional with the type of observational research. The study was conducted in Saudi Arabia at the time of the pilgrimage. The population of this study were all Indonesian Hajj pilgrims in 2015 who were in Saudi Arabia at the time of the study. The research sample was five KBIH. Sampling using the purposive method. Data and information were collected by direct interviews with 300 respondents. Data analysis is done descriptively.Characteristics of research respondents are dominated by men (53%), the proportion of education level of junior and senior high school graduates is 85 percent, marital status shows that most are married by 85 percent. In general, the consumption pattern of fruit and vegetable foods is sufficient, however, there is not enough drinking for the congregation considering the temperature in Saudi Arabia is hotter than in Indonesia. Respondents who had been sick due to overheating/lack of fluids were 81 people (27%) with more than half of them being women as many as 55.4%, 1 person had been treated at BPHI with heat stroke (0.3%),